VETERINARY PHARMACOVIGILANCE SURVEY CONDUCTED IN TAMIL NADU STATE, INDIA – A STATUS REPORT - Ghadevaru Sarath Chandra; V. Suresh Kumar; J. Ramesh (Indian Journal of Veterinary and Animal Sciences Research, 2024)
In India there is no present government policy to survey and evaluate adverse drug events (ADEs) / Pharmacovigilance programme in veterinary medicine. Therefore, essential information such as frequency, severity of treated animal ADRs and reliable data about frequent ADR-producing drugs remains unknown. The objective of the study is to assess and communicate risks and benefits in the market. Ultimately to educate the veterinarians and the stake holders on the safety and efficacy of veterinary drugs and biologicals. To this purpose, a 12 month pilot study based on WHO recommendations was conducted to monitor ADRs in the livestock treated by field veterinarian in the state of Tamil Nadu in India for frequently used drugs and common labeled signs. The present study warrants for the need for sustained veterinary pharmacovigilance programmers in livestock for timely ADR presenting drug reactions and drug safety improvement.